RESPON MASYARAKAT MULTIETNIK TERHADAP KEPEMIMPINAN ADAPTIF DAN INKLUSIF: STUDI FENOMENOLOGI PADA MASYARAKAT ADAT DAN PENDATANG DI PROVINSI LAMPUNG - Allif Panszha Riadi; Pitojo Budiono; Robi Cahyadi Kurniawan (GoAcademica Research dan Publishing, 2026)
This study aims to analyze the responses of multiethnic communities toward adaptive and inclusive leadership and its implications for social justice perceptions in heterogeneous regions. Using a qualitative approach with phenomenological design, this research explores the subjective lived experiences of indigenous and migrant communities in interpreting regional leadership practices in Lampung Province. Data were collected through in-depth interviews and Focus Group Discussions (FGD) conducted separately among ethnic groups. Results show that adaptive leadership is perceived positively when leaders manage conflicts dialogically, respect local values, and demonstrate genuine presence in social dynamics. Inclusive leadership is widely accepted when public services and regional policies provide equal treatment, participatory space, and recognition of multiethnic cultural identities. The study finds that adaptive and inclusive leadership positively correlates with the formation of social justice perceptions, particularly in distributive and procedural dimensions. Procedural justice emerges as the most dominant factor in building social trust and leadership legitimacy. This research reinforces the importance of citizen-centric approaches in leadership studies.